BENTUK PENYAJIAN TARI JEPIN TAMMBONG ENAM DI DESA KARIMUNTING KECAMATAN SUNGAI RAYA KEPULAUAN - Afsari, Regina Ripa; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe problem of this research associates with the presentation of Jepin Tammbong Enam. This study intends to describe the Performance of Jepin Tammbong Enam Dance.The descriptive method was applied with qualitative forms and ethnochoreological approaches. The research data was obtained by observations, documentation, and interviews with Mrs. Suratmi, Mr. Mat'ani, and Mr. Ruslan. The extension of observation and triangulation were utilized as a technique to test the validity of the data with data reduction, presentation, and verification of data.The results of this study revealed that there are three variations of motion and three patterns of Tammbong beats with floor designs in the form of vertical, horizontal and triangular lines along with, on the other hand, flat, straight, angular, symmetrical, low, vertical and deep top designs. The dynamics are not various and have no dramatic design with group compositions using synchronous and balanced designs. The performance requires rhythmic instruments, gambus, rumba and poetry with natural make-up and Telok Belanga, pants, fabric, and headband. The venue for the performance is proscenium, arena, closed stage, and field including Tammbong property.  Keywords : Performance Form, Jepin Tammbong Enam Dance